2021
DOI: 10.6007/ijarbss/v11-i6/10054
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies Used for Reading Skill by Pupils in Selected Rural Schools in Sarawak

Abstract: Rural schools in Malaysia strive to progress on par with their counterparts in urban schools despite their differences. Pupils learning in the rural schools may not experience a similar level of exposure to English as the pupils in the urban schools. It is seen essential to understand the learning process experienced by pupils in rural schools to progress in learning. Language learning strategies are a crucial element in the learning process and action that aid the use and acquisition of language. It is hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…As for the reading skill, affective strategy is the most preferred strategy employed by the students. This result is in line with the study done by (Dawi et al, 2021). As affective strategy deals with students' emotions and feelings during language learning, it is important to note that motivation and a positive learning environment are needed for students to learn the language better.…”
Section: Rq1 -What Is the Preferred Language Learning Strategy In Lea...supporting
confidence: 88%
See 1 more Smart Citation
“…As for the reading skill, affective strategy is the most preferred strategy employed by the students. This result is in line with the study done by (Dawi et al, 2021). As affective strategy deals with students' emotions and feelings during language learning, it is important to note that motivation and a positive learning environment are needed for students to learn the language better.…”
Section: Rq1 -What Is the Preferred Language Learning Strategy In Lea...supporting
confidence: 88%
“…The findings show that the use of learning strategies among Thai university students varies, depending on individual differences and contextual factors. Affective strategy is also the most preferred strategy employed by the respondents in a study done by (Dawi et al, 2021). Lestari and Azizi (2021) also carried out a study to measure LLS employed by university students in Yogyakarta, Indonesia.…”
Section: Studies On Language Learning Strategiesmentioning
confidence: 99%
“…Cohen and Oxford's (1995) Young Learners' Language Strategy Use Survey (YLLSUS) served as the basis for the questionnaire. This version was chosen because the sentences and phrases used were short, concise, and simple to understand for beginners and low intermediate learners (Dawi et al, 2021). These statements were used to assess the language learning strategies utilised by young learners aged 9 to 13.…”
Section: Instrumentmentioning
confidence: 99%
“…Findings have shown that teachers must better grasp second language learning acquisition, as most ESL learners have diverse cultural and linguistic influences. The English language exposure is mainly in the context of the classroom-based learning environment (Dawi et al, 2021). Theories have been formed to find ways to bring language proficiency to a greater level.…”
Section: Literature Reviewmentioning
confidence: 99%